2017
DOI: 10.1097/aap.0000000000000663
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Poststernotomy Pain

Abstract: Chronic pain following median sternotomy is common after cardiac surgery. If left untreated, chronic sternal pain can reduce quality of life, affecting sleep, mood, activity level, and overall satisfaction. This has a significant societal effect given the large number of cardiac surgeries annually. Although a number of pathophysiologic processes and risk factors are assumed to contribute, the exact cause and major risk factors remain unknown. Moreover, the treatment of chronic poststernotomy pain is often inad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
1
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 150 publications
1
30
1
12
Order By: Relevance
“…The patient reported immediate and complete resolution of pain that was maintained for 3 months after the injections. Although parasternal intercostal blocks may reduce acute postoperative pain, there is currently no evidence for their efficacy in preventing chronic poststernotomy pain [25]. For acute sternal fracture analgesia, TTP blocks alone appear to be adequate.…”
Section: Current Indications and Available Evidencementioning
confidence: 99%
“…The patient reported immediate and complete resolution of pain that was maintained for 3 months after the injections. Although parasternal intercostal blocks may reduce acute postoperative pain, there is currently no evidence for their efficacy in preventing chronic poststernotomy pain [25]. For acute sternal fracture analgesia, TTP blocks alone appear to be adequate.…”
Section: Current Indications and Available Evidencementioning
confidence: 99%
“…40 In a subsequent review of postoperative chronic pain prevention, Reddi 41 similarly concluded that ketamine may reduce chronic pain after surgery while suggesting gabapentin and pregabalin as promising but requiring additional robust studies prior to recommendation. In a recent review of chronic poststernotomy pain, Kleiman and colleagues 27 similarly found no evidence to support the use of transdermal lidocaine, glucocorticoids, or dexmedetomidine in decreasing chronic pain. In contrast, the authors acknowledge the effectiveness of acetaminophen, gabapentinoids, and ketamine in providing opioid-sparing analgesia, but describe their utility in preventing chronic poststernotomypain as limited or not yet examined.…”
Section: Rationale For Opioid-sparing Techniquesmentioning
confidence: 99%
“…9,15,16,24 Acetaminophen, gabapentinoids, and ketamine have all been previously described as providing both effective analgesia and offering opioid-sparing benefit. 27,28 Rafiq and colleagues conducted a prospective randomized controlled trial (RCT) examining multimodal analgesics versus opioids following cardiac surgery through median sternotomy. 24 The authors found a combined regimen utilizing dexamethasone, gabapentin, ibuprofen, and acetaminophen provided superior analgesia (decreased numeric rating pain scores) through postoperative day 3 and decreased incidence of nausea and vomiting versus morphine and acetaminophen alone.…”
Section: Rationale For Opioid-sparing Techniquesmentioning
confidence: 99%
See 2 more Smart Citations